2017
DOI: 10.1080/13102818.2017.1369902
|View full text |Cite
|
Sign up to set email alerts
|

CBCT images: an important tool in the analysis of anatomical variations of maxillary sinus related to Underwood septa features

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles ARTICLE; MEDICAL BIOTECHNOLOGY CBCT images: an important tool in the analysis of anatomical variations of maxillary sinus related to Underwood septa features

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…The presence of septa was significantly higher in the middle region in both the right and left sinuses which is consistent with most of the previously reported data as reviewed by Malec et al 10 However, our results are inconsistent with Neychev et al, who found the septa to be more common in the anterior or posterior regions based on the dentate status. 30 The orientation of the majority of maxillary sinus septa in the current study were mediolateral, and the anteroposterior oriented septa were infrequent, which is also consistent with previous studies. 4,19,29,33 The prevalence of complete septa is rare and most if not all septa are partial.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of septa was significantly higher in the middle region in both the right and left sinuses which is consistent with most of the previously reported data as reviewed by Malec et al 10 However, our results are inconsistent with Neychev et al, who found the septa to be more common in the anterior or posterior regions based on the dentate status. 30 The orientation of the majority of maxillary sinus septa in the current study were mediolateral, and the anteroposterior oriented septa were infrequent, which is also consistent with previous studies. 4,19,29,33 The prevalence of complete septa is rare and most if not all septa are partial.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is important to note that Park et al 29 found the prevalence of septa to be higher among females and Neychev et al, found no correlation between gender and the presence of septa. 30 Previous studies have found that there was a positive association between age and the presence of septa. This was also true in the current findings, where 7.3% were found in patients who were younger than 25 years of age versus 61.4% in patients who were 45 years or older.…”
Section: Discussionmentioning
confidence: 97%
“…We also investigated the type of septa and assessed the relationship between tooth loss, infundibulum length, and ostium height. Neychev et al [29] reported that primary complete septa were found in patients with teeth, and secondary partial septa were observed in edentulous patients; in our study, the edentulous patients were found to have a higher prevalence of septa. Our results showed a statistically significant difference between the septa type in toothed and edentulous regions of the maxilla.…”
Section: Discussionsupporting
confidence: 55%
“…Maxillary sinus septa is one of the most studied subjects in terms of location, prevalence, and morphology [27][28][29]. Maxillary sinus septa was found in 49% of patients, on the right (40.2%) and left (33.4%) sides, higher than reported by Kim et al [27], Neugebauer et al [28], but lower than reported by Neychev et al [29]. This difference could be associated with the different radiograph-DOI: 10.1159/000504963 ic examinations, the thin interval slice of the CBCT images (in this study, 0.2-0.4 mm), and the different ages of the study populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation